Pengaruh Modal Sosial Terhadap Kinerja Peternak Kambing Di Desa Besowo, Kecamatan Kepung, Kabupaten Kediri - Naufal Adinar Irsan; Siti Azizah (JURNAL RISET RUMPUN ILMU HEWANI, 2024)
Social capital is an important factor for farmers because it can support the management of livestock businesses in Indonesia. Especially because Indonesian culture still relies heavily on group activities in society. Research on the influence of social capital on the performance of goat breeders in the Besowo Village area aims to describe the characteristics of social capital (Trust, Norm, Network, Reciprocity) by identifying the level of social capital of breeders in Besowo Village, Kepung subdistrict on the performance of the livestock. The research was carried out on 1-28 September 2023 using the Systematic Random Sampling method, namely determining the initial sample randomly using the Slovin formula to obtain 82 respondents in all hamlets in Besowo Village. The results of this research show that social capital has an important role in people's livestock by utilizing the existing social patterns of society.